Efek Penambahan Minuman Air Jeruk Sambal (Citrus Microcarpa) Terhadap Performa Broiler - D. Setiawan; R. Adisti (Jurnal Sain Peternakan Indonesia, 2018)
This research aim to determine the effect of native orange (Citrus microcarpa) to drink water on body weight, feed consumtion and FCR (feed convertion rate). The variables in this study were body weight, feed consumption and feed conversion in broiler. The used materials were day old chick (DOC) strain CP707 as many as 80 birds, were placed in cages with size of (5,5 x 2,5 x 2 m) is partitioned into 20 units an each unit in the experiment with the contents of 4 chickens. Feed used is commercial feed. The method used completely randomized design (CRD), with 4 treatment and 5 replications. with level treatment P0 (commercial feed and 0% native orange for 1 L water), P1 (commercial feed and 0,4 native orange for 1 L water), P2 (commercial feed and 0,8% native oramge for 1 L water) and P3 (commercial feed and 1,2% native orange for 1 L water). Data were analyzed using analysis of variance at level 5% and followed by honesty significant different (HSD). The result showed treatment not significant with body weight, feed consumtion  and FCR (feed convertion rate). Conclusion increment native orange to drink water not significantly on body weight, feed consumtion and FCR (feed convertion rate). Keyword: Citrus microcarpa, Broiler and Performance